Analisis Risiko, Proses, dan Efisiensi Akuntansi Murabahah Pada Pembiayaan KPR di BSI KC Serang - Rasyidin, Elfrida Yuliar; Alifia, Nayla; Pratiwi, Azzahra Zulfa; Putri, Deyna; Jannah, Mukhlishotul (PT Maju Malaqbi Makkarana, 2024)
This study aims to examine the implementation of murabahah accounting in the context of Home Ownership Credit (KPR) financing at Bank Syariah Indonesia (BSI) Serang Branch, with particular emphasis on operational efficiency, transaction transparency, and risks associated with the management of sharia-compliant financing products. Bank Syariah Indonesia, as a financial entity operating in accordance with Islamic sharia principles, uses murabahah contracts in mortgage financing to ensure compliance with the principles of equality and transparency, to prevent usury practices, and to promote community welfare in accordance with the maqashid sharia framework. Throughout this process, murabahah accounting involves the management of credit risk, market risk, and operational risk, all of which require careful supervision to uphold the sanctity of transactions and compliance with Sharia regulations. The methode adopted in this study is qualitative, using a case study approach involving comprehensive interviews with staff and clients at BSI Serang Branch. The findings of the investigation revealed that, while BSI's Sharia-compliant mortgage servicing procedures are implemented with clarity and transparency, challenges related to risk management and accounting efficiency remain significant areas of concern. Consequently, this study contributes to the advancement of sharia accounting practices within financial institutions and enhances the understanding of the challenges faced by banks in administering murabaha-based financing products.